PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA (STUDI PADA KARYAWAN BAGIAN PRODUKSI CV. SARI ALAM LENTENG SUMENEP) - Sulis Amaliyatul Afifah; Abd Kodir Djaelani; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study is to determine effect of occupational safety and health on work productivity employee CV production. Sari Alam Lenteng Sumenep and which variable has a dominant influence on work productivity of CV production employee. Sari Alam Lenteng Sumenep. Data analysis method that used in this research is doubled linear regression. The results of this study concluded that the salvation of work has a significant effect on employee productivity CV. Sari Alam Lenteng Sumenep. The higher level of employee health and safety hence employee productivity in CV. Sari Alam Lenteng Sumenep. R square value of 42.1% means changes in employee productivity change caused by the level of safety and health of employees. The remaining 57.9% was caused by other variables not included in this study. The independent variable that has the highest beta value is work safety variable that is 62.6% sehungga occupational health factor is the dominant factor affecting employee work productivity compared with health work with beta value equal to -26,4%.Keywords: work safety, work healthy, work productivity